A Multimodal Semiotics Approach to The Discourse of Zenius Education Advertisement - Irianti, Yesi (Lembaga Riset Mutiara Akbar, 2024)
The use of semiotics and multimodal approaches in advertising has gained significant traction in recent years. Semiotic multimodality allows individuals to connect with five key systems: linguistic, visual, audio, gestural, and spatial. This study aims to describe the five semiotic modes regarding their purposes and the relationships between verbal and visual texts and messages present in advertisements. The analysis is based on the multimodal semiotic framework proposed by Michèle Anstey and Geoff Bull (2018), which emphasizes these five systems. For this research, three advertisements from Zenius Education's YouTube channel were examined: